Theatre on terror : subject positions in British drama - de Waal, Ariane (Contemporary Drama in English Studies, 2018)
The book series CDE Studies invites monographs (and collections) on issues in contemporary Anglophone dramatic literature and theatre performance. The book series is dedicated to the analysis and renegotiation of contemporary writers and plays and their historical, political, formal, theoretical and methodological contexts.